2009
DOI: 10.1016/j.biopsych.2008.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine-Induced Place Preference in Humans

Abstract: Background-The conditioned place preference procedure is a widely used animal model of rewarding drug effects that, to date, has not been tested in humans. In this study, we sought to demonstrate that humans, like non-humans, would exhibit a preference for a place previously associated with amphetamine. Further, we investigated the relationship between conditioned place preference and the mood-altering effects of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 28 publications
2
75
1
Order By: Relevance
“…Interestingly, the effect persisted for at least 15 days, an aspect that to date has only been consistently demonstrated for drug-related rewards. Considering that the CPP paradigm in now being established in non-human primates (Barros et al, 2013;Monclaro et al, 2014;Valentinuzzi et al, 2008;Wang et al, 2012) and humans (Childs and de Wit, 2009), future studies comparing different food items and evaluating possible long-term effects may play a significant role in elucidating the neural mechanisms underlying the overconsumption of highly palatable foods items (like chocolate).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the effect persisted for at least 15 days, an aspect that to date has only been consistently demonstrated for drug-related rewards. Considering that the CPP paradigm in now being established in non-human primates (Barros et al, 2013;Monclaro et al, 2014;Valentinuzzi et al, 2008;Wang et al, 2012) and humans (Childs and de Wit, 2009), future studies comparing different food items and evaluating possible long-term effects may play a significant role in elucidating the neural mechanisms underlying the overconsumption of highly palatable foods items (like chocolate).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, place preference for amphetamines was demonstrated in humans (Childs and de Wit, 2009). Early research suggested an involvement of D1 dopamine receptors and NMDA-type glutamate receptors in the establishment of cocaine CPP, whereas the AMPA-type glutamate receptors seem to be involved in CPP expression as elucidated by using systemic delivery of specific AMPA and NMDA inhibitors (Cervo and Samanin, 1995).…”
Section: Conditioned Place Preferencementioning
confidence: 99%
“…Studies with laboratory animals have investigated both the acquisition and expression of drug conditioning, but in humans, most studies of drug cues investigate only the expression of drug-related responses, typically in currently or formerly dependent drug users. To date, only a few studies have examined the process of acquisition of conditioning with drugs in humans (eg, Winkler et al, 2011;Childs and de Wit, 2009;. To address this gap, we have developed a novel human drug conditioning paradigm and demonstrated that healthy volunteers acquire a behavioral preference for a stimulus paired with a single dose of a known drug of abuse (ie, methamphetamine (MA) ;Mayo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%